Analisis Keterampilan Proses Sains Siswa dalam Pembelajaran Suhu dan Kalor melalui Metode Praktikum - Septania Nur Farida; Sudarti Sudarti; F. K. A. Anggraeni (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
The 2013 curriculum aims to provide a meaningful learning experience, namely by developing an attitude, knowledge, and skills. This means that knowledge, scientific process skills, and scientific attitudes are very important to be instilled in students. However, learning is still dominated by conventional learning, namely teacher-centered learning (teacher oriented), so that the teacher becomes the only source of knowledge. The purpose of this research is to describe the science process skills of students in learning temperature and heat through the practicum method and to find out if there is an increase in results through the practicum method on the material of temperature and heat. This type of research is descriptive research. This study used a pretest (pretest) and a final test (posttest). The result of the percentage of students' science process skills through practicum is 62.50% with sufficient category. There are 6 indicators of science process skills measured in this study, namely indicators of observation, classification, measuring, communicating, predicting, and concluding. In the observation indicator, the percentage obtained is 58.33% with the less category, the classification indicator is 75.00% in the sufficient category, the measuring indicator is 75.00% in the sufficient category, the communicating indicator is obtained a percentage of 58.33% with poor category, the indicator predicts that a percentage of 58.33% is obtained in the less category, and the indicator concludes that a percentage of 50.00% is obtained in the very poor category. In the pretest results obtained a percentage of 51.39% with a very poor category, while the posttest results obtained a percentage of 62.49% with a sufficient category. From the results of the pretest and posttest, it can be seen that there is an increase in results after learning with the practicum method.